Contribution of Tax Consultancy Firm in the Reduction of Tax Evasion in Cameroon - Tambi Andison Akpor (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2020)
This study attempts to examine the Contribution of Tax Consultancy Firm in the Reduction of Tax Evasion in Cameroon. The objectives are to: explore the contribution of Management of Tax Accounting Consortium (MTA) in the reduction of tax evasion in companies and to investigate the consequences of tax evasion on the tax payer enterprise. Methodologically, we used focus group discussion and quantitative data collected from MTA to estimate our result. The result shows that consultancy firm plays a major role in the reduction of tax evasion. Result by tax payer enterprise shows that companies that evade tax being good, bad or fraudulent faith end up losing much money that may lead to the collapse of the company. We recommend that tax payers should pay their taxes at the appropriate periods and rightly calculated to avoid penalties and interests. The government of Cameroon should absolutely encourage the growth of tax consultancy firms; it’s a wise step towards economic growth.